Antioxidant activity ethanol extract of gotu kola (Centella asiatica (L.) Urban) with DPPH method (2,2-Diphenyl-1-Pikrilhidrazil) - Muhammad Ainul Yahya; Iif Hanifa Nurrosyidah (Universitas Airlangga, 2020)
Unhealthy lifestyles and air pollution cause the number of free radicals in the body to increase. To protect the body from free radicals, there are antioxidant compounds as an antidote and stabilize free radicals. One of the Indonesian plants that can be used as antioxidants is gotu kola (Centella asiatica (L.) Urban. Objective: This study aims to determine the antioxidant activity of the ethanol extract of gotu kola herb using the DPPH (2,2-Diphenyl-1-pikrilhidrazil) method. with IC50 value. Method: Gotu kola (Centella asiatica (L.) Urban) was extracted by the soxhletation method using 96% ethanol solvent. The testing of antioxidant activity was carried out using the DPPH (2.2 Diphenyl-1-Pikrihydrazil) method. Result: Test results of antioxidant activity The ethanol extract of gotu kola herb showed an IC50 value of 78.20 ppm. Conclusion: This indicated that the ethanol extract of gotu kola herb was included in the criteria for strong antioxidants.